Temperature dependenc:e of the spin-lattic:e interaction for Gd3+ in CaF2 and CdF2 - Oseroff, S. B. (American Chemical Society's, 1972)
Fil: Oseroff, S. B. Comisión Nacional de Energía Atómica; Argentina